Factors Related to the Incident Emesis Gravidarum in Pregnancy in the Region Work of Limboto Health Center - Lyssa Khairunnisa Nuwa; Ika Wulansari; Andi Mursyidah (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
Pregnancy is a condition where a woman has a fetus that is growing in the womb. In pregnancy, nausea and vomiting is called emesis gravidarum, which is a condition that occurs due to an increase in the hormones estrogen and progesterone. If not treated, this emesis gravidarum will increase to hyperemesis gravidarum. This study aims to determine the factors related to the incidence of emesis gravidarum in pregnancy in the working area of the Limboto Health Center. The research design used in this study is to use quantitative research with a cross sectional approach. The sample in this study was 35 respondents using the total sampling technique. The results of this study using the Fisher Exact Test were obtained at the age variables p-value 0.039 (<0.05), work p-value 0.029 (<0.05), psychological p-value 0.020 (<0.05), family support p-value 0.043 (<0.05) which means that there is a significant relationship between age, work, psychology, and family support with the incidence of emesis gravidarum in pregnancy. The suggestion from this study is that it can be used in increasing knowledge about knowing the factors related to the incidence of emesis gravidarum in pregnancy in the working area of the Limboto Health Center.